On inverse problem of closure of differential systems with degenerate diffusion - Tleubergenov, Marat; Ibraeva, Gulmira (Eurasian Mathematical Journal, 2019)
The quasi-inversion method is used to obtain necessary and sufficient conditions for the solvability of the inverse closure problem in the class of stochastic differential Itô systems of the first order with random perturbations from the class of processes with independent increments and diffusion degenerate with respect to a part of the variables.